Power-Efficient UAV Base Station Placement Considering Position and Accessibility of Individual Nodes - Park, Jaehyong; Baek, Hoki; Choi, Seonjoo; Lim, Jaesung; Lee, Choong Hee; Park, Hyung Won (Journal of Korean Institute of Communications and Information Sciences, 2021)
Recently, unmanned aerial vehicle base stations (UAV-BSs) have been widely studied as a means of providing wireless cellular networks. We propose an energy efficient UAV-BS placement scheme considering a position and an access probability of individual nodes. We consider different access probabilities of each node because the UAV-BS has different traffic for node. we aim to minimize the average transmit power of the UAV-BS considering the difference in access probability where there is different network traffic from the UAV-BS to a node. A UAV-BS should fly high enough to ensure a line-of-sight (LOS) link for providing reliable communication to users, whereas it should fly low to save energy. Therefore, in this paper, we propose three step algorithm by formulation it as a Weber problem and solving a distance-and-weight function while considering these two constraints. We evaluate the performance through simulation and the results show that the proposed scheme provides lower average transmit power than the maximal coverage algorithm.
Keywords: base station; gateway; location; placement; Unmanned aerial vehicle (UAV); Weber problem